Animal sourced foods and child stunting - Headey, Derek D.; Hirvonen, Kalle; Hoddinott, John F. (Oxford University Press, 2018)
Stunting affects 160 million pre-school children globally with adverse life-long consequences. While work within nutritional science suggests that stunting in early childhood is associated with low intakes of animal-sourced foods (ASFs), this topic has received little attention from economists. We attempt to redress this omission through an analysis of 130,432 children aged 6–23 months from 49 countries. We document distinctive patterns of ASF consumption among children in different regions. We find evidence of strong associations between stunting and a generic ASF consumption indicator, as well as dairy, meat/fish, and egg consumption indicators, and evidence that consuming multiple ASFs is more advantageous than any single ASF. We explore why ASF consumption is low but also so variable across countries. Non-tradable ASFs (fresh milk, eggs) are a very expensive source of calories in low-income countries and caloric prices of these foods are strongly associated with children’s consumption patterns. Other demand-side factors are also important, but the strong influence of prices implies an important role for agricultural policies—in production, marketing and trade—to improve the accessibility and affordability of ASFs in poorer countries.